ANALISIS YURIDIS PERJANJIAN KEMITRAAN LAHAN PERKEBUNAN SAWIT (STUDI PADA PT. GUNUNG MELAYU)ANALISIS YURIDIS PERJANJIAN KEMITRAAN LAHAN PERKEBUNAN SAWIT (STUDI PADA PT. GUNUNG MELAYU) - AGUS PERWIRA (PREMISE LAW JURNAL, 2017)
In this case, there is a partnership contract between PT.GunungMelayu and some people, and one of them is NintangSurbakti. Partnership contract can cause loophole in law; namely, the clause which contains cooperation, but the people are burdened with various kinds of production and maintenance costs which are considered as their debt to the company. The conclusion of the research was that partnership contract on plantation is regulated in Law No. 39/2014 on Plantation and Law No. 20/2008 on Micro, Small, and Medium Enterprises. Replanting the plants in the plantation harms the people so that it is considered as default. It is recommended that the Government revise the substance of the regulation on partnership contract. The management of the company should pay attention to the principle of partnership which benefits and strengthens each other in the partnership contract with the farmers. Keywords: Partnership, Partnership Contract, Oil Palm Plantation